Klausa Dalam Novel Marveluna Lets Fly Together Karya Ita Krn - Septiani, Anggri; Gunawan, Hafiz; Atmaja, Loliek Kania; Ariyanti, Tri Dina (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aimed to determine the types of clauses, the structure of the clause and the function of the clause in the novel of Marveluna Lets Fly Together by Ita Krn. This study used qualitative descriptive method. The data collection technique of this study was documentation technique. The data in this study were sentences containing the types, structures and functions of clauses in the novel Marveluna Lets Fly Together by Ita Krn. The results of this study show that there are 727 data, 642 verbal clauses, 15 nominal clauses, 57 adjective clauses, 4 prepositional clauses and 9 numeral clauses. The types of verbal clauses consist of 396 data incomplete targeted action verbal clauses, 22 data complete targeted action verbal clauses, 196 data non-targeted action verbal clauses and 25 data situation clauses, the verbal clauses that were not found were event verbal clauses. The noun clause consists of a clause that states the type of noun 5 data, states the name of the noun 6 data, states the relationship of 2 data, and states the characteristics or special characteristics of 2 data. The noun clause of the profession is not found. The adjective clause consists of 17 data physical states, 5 data mental attitudes and 34 data internal feelings. The clause structure of this study is S+P, S+P+O, S+P+O+Pel, S+P+O+K and S+P+K. Function. The clauses of this study consist of the function of S as the actor of the activity, the function of P as a verb, O as something that is done or is the target of the subject, K as additional information and Pel as perfecting the predicate but not subject to the subject's actions.